Parenting Patterns and Adolescent Self-Efficacy in Prevention of HIV/AIDS Risky Behavior - Enggal Hadi Kurniyawan; Lisnawati; Ahmad Rifai; Nur Widayati; Hanny Rasni; Erti Ikhtiarini Dewi; Emi Wuri Wuryaningsih (KHD Production, 2023)
The parenting style given by parents is inappropriate, it will have an impact on the occurrence of HIV/AIDS risky behavior in adolescents. One of the main factors causing risky behavior in adolescents is the low level of self-efficacy in staying away from risky behavior. This study aimed to analyze the relationship between parenting style and self-efficacy in preventing HIV/AIDS risk behavior in adolescents. The design in this study is a descriptive correlation with a cross-sectional approach. The sampling technique used in this study was proportionate stratified random sampling. Respondents in this study were teenagers at Darus Sholihin Puger Jember Vocational School, many as 84 respondents. Parenting style was measured using a parenting style questionnaire. Self-efficacy was measured using the Self-Efficacy Questionnaire for Prevention of HIV/AIDS Risky Behavior. The analysis in this study used the Chi-square test. The parenting style that is widely applied to adolescents is democratic parenting, and the majority have self-efficacy while preventing HIV/AIDS risky behavior. There is a significant relationship between parenting style and self-efficacy in preventing HIV/AIDS risky behavior with a p-value of 0.026. Health services can educate parents about the importance of parenting to increase self-efficacy in adolescents, especially in terms of preventing HIV/AIDS risky behavior.